Network Edge Computing Framework for Application Deployment - Supriya Pal, Thyagarajamurthy A. (International Journal of Advanced Science and Technology, 2020)
The Network Edge Framework is a system for stand-in open association and device novelties at the edge of the network. It is a platform available for designing and deploying edge applications and services within the system. It also makes it easier for developers to captivate by creating new 5G edge use cases and services with a common ecosystem of hardware, software and solution integrators. This paper explores the complexities of the network for cloud developers. With an intuitive web-based interface, it enables safe onboarding and system management. It facilitates features such as terminating access, directing traffic, multi-tenancy systems, server registry, server authentication, telemetry, application frameworks, machine detection and control. Since the applications are deployed on the edge node, the latency and bandwidth can be reduced